Systemic Inflammatory Effects of Traumatic Brain Injury, Femur Fracture, and Shock: An Experimental Murine Polytrauma Model. (4th March 2012) - Probst, C.; Mirzayan, M. J.; Mommsen, P.; Zeckey, C.; Tegeder, T.; Geerken, L.; Maegele, M.; Samii, A.; van Griensven, M.
Abstract : Objective . Despite broad research in neurotrauma and shock, little is known on systemic inflammatory effects of the clinically most relevant combined polytrauma. Experimental investigation in an animal model may provide relevant insight for therapeutic strategies. We describe the effects of a combined injury with respect to lymphocyte population and cytokine activation. Methods . 45 male C57BL/6J mice (mean weight 27 g) were anesthetized with ketamine/xylazine. Animals were subjected to a weight drop closed traumatic brain injury (WD-TBI), a femoral fracture and hemorrhagic shock (FX-SH). Animals were subdivided into WD-TBI, FX-SH and combined trauma (CO-TX) groups. Subjects were sacrificed at 96 h. Blood was analysed for cytokines and by flow cytometry for lymphocyte populations. Results . Mortality was 8%, 13% and 47% for FX-SH, WD-TBI and CO-TX groups (P < 0.05 ). TNFα (11/13/139 for FX-SH/WD-TBI/CO-TX; P < 0.05 ), CCL2 (78/96/227; P < 0.05 ) and IL-6 (16/48/281; P = 0.05 ) showed significant increases in the CO-TX group. Lymphocyte populations results for FX-SH, WD-TBI and CO-TX were: CD-4 (31/21/22; P = n.s.), CD-8 (7/28/34, P < 0.05 ), CD-4-CD-8 (11/12/18; P = n.s.), CD-56 (36/7/8; P < 0.05 ). Conclusion . This study shows that a combination of closed TBI and femur-fracture/ shock results in an increase of the humoral inflammation. More attention to combined injury models in inflammation research is indicated.